(untitled) (American Journal of Pedagogical and Educational Research, 2026)
The article analyzes the didactic features of using the graphical visualization method in the process of forming professional competence of students in technical specialties. The pedagogical potential of the method in teaching technical disciplines and its role in developing students’ professional competence is highlighted. The study results show that the systematic application of the graphical visualization method can increase the efficiency of the learning process.